Innovative methods of teaching for English for Specific Purposes students - Dildorxon Inomidinova Ikramovna (Euro Asian Journal Publishing, 2024)
This article explores innovative methods to enhance the teaching of English for Specific Purposes (ESP) by incorporating cutting-edge approaches and technologies. The study aims to analyze current literature on ESP education, introduce novel teaching methods, present the results of their implementation, and discuss their implications for ESP learners. The findings offer valuable insights into the potential benefits of innovation in ESP education and provide recommendations for future practices.
Keywords: English for Specific Purposes; innovative teaching methods; language acquisition